Multi-scale intelligent fusion and dynamic validation for high-resolution seismic data processing in drilling - Sanyi YUAN; Yanwu XU; Renjun XIE; Shuai CHEN; Junliang YUAN (Petroleum Exploration and Development)
During drilling operations, the low resolution of seismic data often limit the accurate characterization of small-scale geological bodies near the borehole and ahead of the drill bit. This study investigates high-resolution seismic data processing technologies and methods tailored for drilling scenarios. The high-resolution processing of seismic data is divided into three stages: pre-drilling processing, post-drilling correction, and while-drilling updating. By integrating seismic data from different stages, spatial ranges, and frequencies, together with information from drilled wells and while-drilling data, and applying artificial intelligence modeling techniques, a progressive high-resolution processing technology of seismic data based on multi-source information fusion is developed, which performs simple and efficient seismic information updates during drilling. Case studies show that, with the gradual integration of multi-source information, the resolution and accuracy of seismic data are significantly improved, and thin-bed weak reflections are more clearly imaged. The updated seismic information while-drilling demonstrates high value in predicting geological bodies ahead of the drill bit. Validation using logging, mud logging, and drilling engineering data ensures the fidelity of the processing results of high-resolution seismic data. This provides clearer and more accurate stratigraphic information for drilling operations, enhancing both drilling safety and efficiency.